Kidney biopsy in pregnancy: evidence for counselling? A systematic narrative review. Issue 4 (15th January 2013) - Piccoli, GB; Daidola, G; Attini, R; Parisi, S; Fassio, F; Naretto, C; Deagostini, MC; Castelluccia, N; Ferraresi, M; Roccatello, D; Todros, T
<x xml:space="preserve">Abstract</x> Background Kidney diseases, which have a prevalence of 3% in women of childbearing age, are increasingly encountered in pregnancy. Glomerulonephritis may develop or flare up in pregnancy, and a differential diagnosis with pre‐eclampsia may be impossible on clinical grounds. Use of kidney biopsy is controversial, but a systematic review has not been carried out to date. Objectives To review the literature on kidney biopsy in pregnancy, with a focus on indications, risks and timing. Search strategy Medline, Embase, CHINAL and the Cochrane Library were searched in September 2012, with 'pregnancy' and 'kidney biopsy' used as MESH and free terms, for the period 1980–2012. Results were filtered for 'human' if this option was available. Selection criteria Biopsies during pregnancy and within 2 months after delivery. Case reports (fewer than five cases) and kidney grafts were excluded. Paper selection was performed in duplicate. Data collection and analysis Data were extracted in duplicate. The high heterogeneity in study design necessitated that the review be narrative, except for data on adverse events, which were analysed with regard to the timing of kidney biopsy. Main results Of 949 references, 39 were selected, providing data on 243 biopsies in pregnancy and 1236 after delivery (timing was unclear in 106 women). The main aims of the studies were to define morphology in pre‐eclampsia (23 studies), to carry out a risk–benefit analysis of kidney biopsy (11 studies), and to investigate pregnancy‐related acute kidney injury (five studies). Four cases of major bleeding complications occurred at 23–26 weeks of gestation. Relevant complications were observed in 7% of women during pregnancy and 1% after delivery (P = 0.001). Kidney biopsy performed for the diagnosis of glomerulonephritis or pre‐eclampsia led to therapeutic changes in 66% of cases. Authors' conclusions The evidence on kidney biopsy in pregnancy is heterogeneous, but a significantly higher risk of complications (relative to postpartum biopsy) was found, with a possible peak at around 25 gestational weeks.